2021
DOI: 10.1038/s41467-021-22770-4
|View full text |Cite
|
Sign up to set email alerts
|

RHOA signaling defects result in impaired axon guidance in iPSC-derived neurons from patients with tuberous sclerosis complex

Abstract: Patients with Tuberous Sclerosis Complex (TSC) show aberrant wiring of neuronal connections formed during development which may contribute to symptoms of TSC, such as intellectual disabilities, autism, and epilepsy. Yet models examining the molecular basis for axonal guidance defects in developing human neurons have not been developed. Here, we generate human induced pluripotent stem cell (hiPSC) lines from a patient with TSC and genetically engineer counterparts and isogenic controls. By differentiating hiPSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 80 publications
0
15
0
Order By: Relevance
“…Recent research in a TSC2 knockout iPSC model confirms the altered excitatory/inhibitory imbalance as observed in animal models, which is attributed to an increase in GABAergic signaling at inhibitory synapses [147]. However, neuronal growth cone studies in neurons derived from iPSCs report TSC2 heterozygous knockouts to have normal mTOR signaling but abnormal axon extension and insensitivity to inhibitory axonal guidance cues suggesting mTOR downstream processes to be the culprit and not necessarily mTOR itself [148].…”
Section: Cell Models Of Mtoropathies 411 Tscmentioning
confidence: 86%
“…Recent research in a TSC2 knockout iPSC model confirms the altered excitatory/inhibitory imbalance as observed in animal models, which is attributed to an increase in GABAergic signaling at inhibitory synapses [147]. However, neuronal growth cone studies in neurons derived from iPSCs report TSC2 heterozygous knockouts to have normal mTOR signaling but abnormal axon extension and insensitivity to inhibitory axonal guidance cues suggesting mTOR downstream processes to be the culprit and not necessarily mTOR itself [148].…”
Section: Cell Models Of Mtoropathies 411 Tscmentioning
confidence: 86%
“…To truly determine whether MS iPSC derived neurons possess intrinsic deficiencies that contribute to MS pathology, more cell lines need to be subjected to differentiation methods that produce specific neuronal subtypes. Intrinsic changes in neuron function have been identified using iPSCs generated from people with other neurological conditions, such as Parkinson's disease (Carola et al, 2021), autism spectrum disorder (Lim et al, 2021) and tuberous sclerosis complex (Catlett et al, 2021). Characterising the earliest drivers of neuron pathology will be critical for developing neuroprotective therapies for MS and this could be achieved by studying MS iPSC-derived neurons.…”
Section: Is Neuron Function Inherently Impaired In People With Ms?mentioning
confidence: 99%
“…2018; Winden et al, 2019;Martin et al, 2020;Catlett et al, 2021;Hisatsune et al, 2021). Hamartomas are potentially caused by "second-hit" somatic mutations in Tsc1 or Tsc2 resulting in loss of heterozygosity (LOH) (Consortium, 1993;Sepp et al, 1996;van Slegtenhorst et al, 1997).…”
Section: New Insights Into the Neurodevelopmental Origin And Heteroge...mentioning
confidence: 99%
“…The inheritance of TSC is autosomal dominant and can be caused by germline mosaicism, although most cases result from de novo mutations during early development ( Rose et al, 1999 ; Orlova and Crino, 2010 ). Interestingly, hiPSC models have shown that neurons with heterozygous Tsc1/2 mutations exhibit atypical morphology, defects in differentiation and axon guidance, and altered excitability and synaptic function ( Li et al, 2017a ; Sundberg et al, 2018 ; Zucco et al, 2018 ; Nadadhur et al, 2019 ; Catlett et al, 2021 ; Hisatsune et al, 2021 ). Homozygous loss of Tsc1/2 in hiPSC-derived neurons generally enhances these phenotypes ( Sundberg et al, 2018 ; Winden et al, 2019 ; Martin et al, 2020 ; Catlett et al, 2021 ; Hisatsune et al, 2021 ).…”
Section: New Insights Into the Neurodevelopmental Origin And Heteroge...mentioning
confidence: 99%
See 1 more Smart Citation